"The Theme of Love between the Poem ‘Hiziya’ by Mohamed Ben Guittoun and the Play Romeo and Juliet by William Shakespeare — A Comparative Study." - saadi, seid.; .benbouza, malika (El Omda in Linguistics and Discourse Analysis, 2026)
with William Shakespeare's play Romeo and Juliet from English heritage, with the aim of drawing consensus and difference in love between Arab and English cultures, as well as the artistic template of the two literary genres. Each culture has its own, and the applied aspect has examined the similarities and differences in form and content between the two literary texts, and in the latter we have concluded that the subject of love is a common human universal topic despite cultural difference.